Comparative study on flow localization using a damage model and a post-processing plastic instability code for prediction of failure in sheet metal forming - Pedro Manuel Cardoso Teixeira (2007)
Formability prediction in sheet metal forming processes is an important demand from industry, since such assessment defines the success of a stamping process. The ability to predict the formability limit is of major importance in order to optimize the process, examine the influence of each parameter on the necking occurrence and consequently to improve the press performance. In this work, Lemaitres ductile damage model is implemented in Abaqus /Explicit code in order to compare the performance of this coupled approach with the traditional use of FLDs. These are usually employed as an a posteriori analysis of the finite element solution in which the necking phenomenon is carried out in the framework of Marciniak-Kuczinsky analysis coupled with the theory of plasticity. The previous strategies are compared with an experimental failure case.